A Lead‐free Organicnorganic Halide Perovskite Absorber with Photoconductive Response. Issue 20 (23rd September 2020) - Wang, Yuyin; Han, Shiguo; Liu, Yi; Li, Yaobin; Sun, Zhihua; Luo, Junhua
Abstract: Perovskite hybrids of lead organometal halides, (e. g., CH3 NH3 PbX3, X=Cl, Br, I) have gained wide attention since their spectacular progress on optoelectronic technologies in recent years. However, it still remains the fundamental problem, namely, the existence of the toxic, bioaccumulative, polluting element Pb and the instability of humidity. In particular, the use of toxic Pb severely limits the broad applications and commercialization of lead‐containing optoelectronic devices, and finding an alternative that preserves the unique optoelectronic properties of the lead halide perovskite is highly urgent. Bi 3+ exhibits isoelectronic behavior similar to that of Pb 2+ in terms of ion radius and electronegativity, which is expected as an environmentally friendly alternative for lead. However, 1D Bi‐based hybrid organic‐inorganic light‐absorbing materials with pyridinium are not numerous. Although great progress has been made, the research on photoresponse behavior are still rarely reported. Here, we present a lead‐free organic‐inorganic hybrid absorber with photoconductive response, (C5 H7 N2 )BiI4 (1, C5 H7 N2 + is 2‐aminopyridinium), which displays a narrow optical bandgap of ∼1.8 eV. Equally importantly, 1 not only features highly applicable properties, but is also able to absorb across most of the UV/Vis region of the solar spectrum. Furthermore, high‐quality single crystal with sizes up to 7×6×4 mm 3 was successfully grown. In addition, 1 exhibited extremely low dark current (2×10 −11  A) at the bias of 10 V, which indicates that the indicator of 1 is an order of magnitude lower than other reported perovskite photodetectors. Moreover, photocurrent on/off switches is faster (∼670 ms), indicating that 1 can be a promising photosensitive switch. These intriguing properties, namely the lead‐free composition, a small band gap, and the fast photoconductive response, suggest promising applications in the field of optoelectronics. Abstract : A lead‐free organic‐inorganic hybrid perovskite, (C5 H7 N2 ) BiI4 (1, C5 H7 N2 + is 2‐aminopyridinium), exhibits a remarkable photoresponse under light illumination. 1 not only features highly applicable properties but is also able to absorb across most of the UV/Vis region of the solar spectrum. High‐quality single crystal with sizes up to 7×6×4 mm 3 was successfully grown, which exhibited extremely low dark current (2×10 −11  A) at the bias of 10 V.